Direct and Indirect Effects of Training Vouchers for the Unemployed - Martin Huber; Michael Lechner; Anthony Strittmatter (Institute for the Study of Labor (IZA), 2015)
This paper evaluates the effect of a voucher award system for assignment into vocational training on the employment outcomes of unemployed voucher recipients in Germany, along with the causal mechanisms through which it operates. It assesses the direct effect of voucher assignment net of actual redemption, which may be driven by preference shaping/learning about (possibilities of) human capital investments or simply by costs of information gathering. Using a mediation analysis framework based on sequential conditional independence assumptions and semiparametric matching estimators, our results suggest that the negative short term and positive long term employment effects of voucher award are mainly driven by actual training participation. However, also the direct effect of just obtaining the voucher is negative in the short run. This points to potential efficiency losses of voucher award systems if individuals decide not to redeem, as employment chances are lower than under non-award in the short run and under redemption in the long run, making non-redemption the least attractive option.
Keywords: J64; J68; C21; C31; 330; mediation analysis; voucher award; training programmes; direct effects; indirect effects; causal mechanisms; causal channels; matching estimation